Carbon dioxide emission and developing countries: a dynamic panel data / Siti Ayu Jalil - Jalil, Siti Ayu (UiTM Cawangan Johor, 2019)
This study investigates the determinants of carbon dioxide (CO2) emissions in selected 126 developing countries based on a dynamic panel data model. It employs the Generalized Method of Moments (GMM) technique and the analysis covers countries situated in Africa, Latin America and the Caribbean, Middle East and North Africa, and Asia and the Pacific region from year 1971 to 2009. The results show per capita gross domestic product, energy usage, energy consumption from fossil fuel-based, foreign direct investment, urbanization, industrial production, agriculture production and education level have significant impact on the growth of carbon emissions. Government in developing countries seems to centralize their focus on energy conservation type of policies to cut carbon emission. The move to emphasize on stringent environmental regulations and energy policies is much needed as to ensure all aspects must be addressed to reduce the carbon emission in the region.